Inclusive math practices in primary school. Twelfth Congress of the European Society for Research in Mathematics Education - Häsel-Weide, Uta; Nührenbörger, M. (Twelfth Congress of the European Society for Research in Mathematics Education (CERME12))

(Selbst-)Einschätzungen zum Herausforderungsbereich Digitalisierung in Schule und Hochschule – Eine empirische Online-Befragung bei Sachunterrichtsstudierenden an der Universität Paderborn - Brenke, Laurien; Kirsch, Alexander; Blumberg, Eva (GDSU-Journal)

Effekte des Feedbacks von Lehrkräften auf die Selbstwirksamkeitsüberzeugungen und die intrinsische Motivation von Kindern im naturwissenschaftlichen Sachunterricht der Grundschule. Vortrag. 30. Jahrestagung der Kommission "Grundschulforschung und Pädagogik der Primarstufe" der Deutschen Gesellschaft für Erziehungswissenschaft (DGfE, Sektion Schulpädagogik). Thema: "Nachhaltige Bildung in der Grundschule" - Hoya, Fabian Karl; Schulze, Jan Roland; Blumberg, Eva; Hellmich, Frank

Pre-service teachers’ team-teaching practices and children’s competence development in inclusive schools. Single Paper. EARLI SIG 11 Conference 2022 ‘Teaching and Teacher Education’. “Digital Transformation in Teaching and Teacher Education” - Hellmich, Frank; Hoya, Fabian Karl; Schulze, Jan Roland; Blumberg, Eva

DiPoSa: Didaktisch-diagnostische Potentiale des inklusionsorientierten Sachunterrichts: Identifizieren, Konzeptualisieren und Implementieren. Vortrag auf der Auftaktveranstaltung zur BMBF-Förderrichtlinie „Förderbezogene Diagnostik in der inklusiven Bildung“ im Rahmen des BMBF-Metavorhabens „Qualifizierung für inklusive Bildung“ - Schroeder, René; Blumberg, Eva; Miller, Susanne; Kottmann, Brigitte; Reh, Anne; Franzen, Katja

Unternehmenszusammenschlüsse von Supermärkten - eine wettbewerbspolitische Analyse am Beispiel von Edeka und Kaiser's Tengelmann - Erdogan, Yeliz

Zum Potenzial von Kryptowährungen. Eine ökonomische Analyse zu den Chancen und Risiken digitaler Währungen - Perampalam, Abirame

Mergers on digital markets - An economic analysis - Nassar, Hamza

Differenz in der fachschulischen Ausbildung frühpädagogischer Fachkräfte - Kuhn, Mealnie; Landhäußer, Sandra (Heterogenität in Bildung und Differenz in Kindheits- und Sozialpädagogik)
Heterogenität und Differenz sind zentrale und etablierte Begriffe und Konzepte in erziehungswissenschaftlichen Diskursen. Wenngleich diese zum Teil sehr unterschiedlich genutzt werden, sind damit stets Thematisierungsweisen von Unterschieden und Unterscheidungen in pädagogischen Kontexten angesprochen. Dies greift der Band auf und thematisiert verschiedene Zugänge zu Heterogenität und Differenz sowie die damit in Verbindung stehenden Differenzkategorien, Begriffe und Konzepte in kindheits- und sozialpädagogischen Zusammenhängen. Neben theoretischen Beiträgen werden in empirischen Analysen verschiedene Aspekte des Heterogenitäts- und Differenzdiskurses in der Kindheits- und Sozialpädagogik beleuchtet und diskutiert.
Keywords: Sozialpädagogik; frühpädagogischer Fachkräfte; frühpädagogischer Fachkräfte

Technology Education in Elementary School Using the Example of 'Learning Robots' – Development and Evaluation of an In-Service Teacher Training Concept. - Janicki, Nicole; Tenberge, Claudia

Grade 6 Students’ Perception and Use of Data-Based Decision Trees - Podworny, Susanne; Fleischer, Yannik; Hüsing, Sven (Bridging the Gap: Empowering and Educating Today’s Learners in Statistics. Proceedings of the Eleventh International Conference on Teaching Statistics)
Decision-making processes are often based on data and data-driven machine learning methods in different areas such as recommender systems, medicine, criminalistics, etc. Well-informed citizens need at least a minimal understanding and critical reflection of corresponding data-driven machine learning methods. Decision trees are a method that can foster a preformal understanding of machine learning. We developed an exploratory teaching unit introducing decision trees in grade 6 along the question “How can Artificial Intelligence help us decide whether food is rather recommendable or not?” Students’ performances in an assessment task and self-assessment show that young learners can use a decision tree to classify new items and that they found the corresponding teaching unit informative.

Aktuelle Entwicklungen in der Lehrer:innenbildung für Inklusion: Herausforderungen – Konzepte – Perspektiven. Keynote an der Tagung: Lehrer:innenbildung für Inklusion – Hochschuldidaktische Konzepte und Perspektiven an der Pädagogischen Hochschule Heidelberg - Büker, Petra
September 2022

Als Sozialforscher*innen die eigene Schule evaluieren und mitgestalten: Kindersichten auf ein partizipatives Setting in der Grundschule - Büker, Petra; Hüpping, Birgit (Mitbestimmung von Kindern. Grundlagen für Unterricht, Schule und Hochschule)

Reflexion und Reflexivität im Kontext Grundschule. Perspektiven für Forschung, Lehrer:innenbildung und Praxis

Catalytic Properties of High Nitrogen Content Carbonaceous Materials - Lepre, Enrico; Rat, Sylvain; Cavedon, Cristian; Seeberger, Peter H.; Pieber, Bartholomäus; Antonietti, Markus; Lopez Salas, Nieves (Angewandte Chemie International Edition)
Keywords: General Chemistry; Catalysis

Mn(ii) sub-nanometric site stabilization in noble, N-doped carbonaceous materials for electrochemical CO2 reduction - Kossmann, Janina; Sánchez-Manjavacas, Maria Luz Ortiz; Brandt, Jessica; Heil, Tobias; Lopez Salas, Nieves; Albero, Josep (Chemical Communications)
The reported N-doped noble carbonaceous support provides strong stabilization of Mn( ii ) sub-nanometric active sites as well as a convenient coordination environment to produce CO, HCOOH and CH 3 COOH from electrochemical CO 2 reduction.
Keywords: Materials Chemistry; Metals and Alloys; Surfaces; Coatings and Films; General Chemistry; Ceramics and Composites; Electronic; Optical and Magnetic Materials; Catalysis

Efficient ethanol electro-reforming on bimetallic anodes supported on adenine-based noble carbons: hydrogen production and value-added chemicals - Rodríguez-Gómez, Alberto; Lepre, Enrico; Dorado, Fernando; Sanchez-Silva, Luz; Lopez Salas, Nieves; de la Osa, Ana Raquel (Materials Today Energy)
Keywords: Energy Engineering and Power Technology; Fuel Technology; Nuclear Energy and Engineering; Materials Science (miscellaneous); Renewable Energy; Sustainability and the Environment

Constructing Interfacial Boron‐Nitrogen Moieties in Turbostratic Carbon for Electrochemical Hydrogen Peroxide Production - Tian, Zhihong; Zhang, Qingran; Thomsen, Lars; Gao, Nana; Pan, Jian; Daiyan, Rahman; Yun, Jimmy; Brandt, Jessica; Lopez Salas, Nieves; Lai, Feili; Li, Qiuye; Liu, Tianxi; et al. (Angewandte Chemie International Edition)
Keywords: General Chemistry; Catalysis

Overcoming Electron Transfer Efficiency Bottlenecks for Hydrogen Production in Highly Crystalline Carbon Nitride‐Based Materials - Teixeira, Ivo F.; Tarakina, Nadezda V.; Silva, Ingrid F.; Lopez Salas, Nieves; Savateev, Aleksandr; Antonietti, Markus (Advanced Sustainable Systems)
Keywords: General Environmental Science; Renewable Energy; Sustainability and the Environment

Ni-based electrocatalysts for unconventional CO2 reduction reaction to formic acid - Lepre, Enrico; Heske, Julian; Nowakowski, Michal; Scoppola, Ernesto; Zizak, Ivo; Heil, Tobias; Kühne, Thomas D.; Antonietti, Markus; Lopez Salas, Nieves; Albero, Josep (Nano Energy)
Keywords: Electrical and Electronic Engineering; General Materials Science; Renewable Energy; Sustainability and the Environment